No Room for Dissent: Domesticating WhatsApp, Digital Private Spaces, and Lived Democracy in India. Issue 1 (10th November 2021) - Williams, Philippa; Kamra, Lipika; Johar, Pushpendra; Khan, Fatma Matin; Kumar, Mukesh; Oza, Ekta
Abstract: WhatsApp and digital private spaces are transforming the quality of lived democracy in India today. Bringing together STS, geographies of democracy, digital and political anthropology, and feminist approaches to the home, this paper makes visible how the Silicon Valley imaginary of the "digital living room" is domesticated in India. Drawing on digital ethnographic research in urban north India we show how WhatsApp is being used by the Hindu right to digitise new party‐political intimacies. This has implications for how people at the margins of Hindu nationalist politics dwell in the "digital living room". Framed as a home like space, we problematise Facebook's "spatiotechnical" utopia by making visible how kinship and (domestic) politics are newly entangled in digital private spaces. Finally, we document how WhatsApp is deployed as a technology of discipline to determine modes of appropriate sociality and reconfigure spaces of digital‐physical inclusion/exclusion in the making of India's "ethnic democracy". Resumo: O WhatsApp e outros espaços privados digitais estão transformando a qualidade da democracia na Índia hoje. Este artigo parte dos campos CTS (Ciência, Tecnologia e Sociedade), geografias da democracia, antropologia digital e política, e abordagens feministas para o doméstico para mostrar como o imaginário da "sala de estar digital" do Vale do Silício é domesticado na Índia. Com base em etnografia digital no norte urbano da Índia, mostramos como o WhatsApp vem sendo utilizado pela direita hinduísta para digitalizar novas intimidades político‐partidárias. Isso tem implicações para o modo como as pessoas às margens das políticas nacionalistas hinduístas habitam a "sala de estar digital". Entendida enquanto um espaço similar ao doméstico, nós problematizamos a utopia "espaço‐técnica" do Facebook visibilizando como o parentesco e a política (doméstica) se rearticulam em espaços privados digitais. Finalmente, documentamos como o WhatsApp é empregado como tecnologia de disciplina que determina os modos de apropriação da socialidade, e reconfigura espaços de inclusão/exclusão física‐digital no processo de construção da "democracia étnica" na Índia.